EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SMK NEGERI 5 PADANG - Gerry Lyman Tambunan; Rizky Ema Wulansari; Ambiyar Ambiyar; Remon Lapisa (Jurnal Vokasi Mekanika (VoMek), 2024)
A key factor in improving the caliber of human resources is education. Enhancing the quality of education is believed to foster a more competent and superior workforce. Although there is no denying the importance between educators and learners along the educational journey, many educational institutions still struggle to provide their students with high-quality learning. This research delves into the effectiveness of video media in excellenceing Student Learning Outcomes. Research was carried out in a Grade 11 class for regarding of Milling Machine Methods at SMK Negeri 5 Padang. Two distinct classes were involved: an experimental class that utilized video media and control class that did not. The study used a post-test only control group design and the quasi-experimental research methodology. Data was gathered through post-test assessments and analyzed using descriptive analysis, normality tests, homogeneity tests, hypothesis tests. Analysis's findings demonstrated that the students in the experimental class had average post-test scores (78.19) were significantly higher than those of the control class (63.03). Statistical data obtained from the hypothesis tests convincingly demonstrated a substantial improvement in the learning outcomes of students who integrated video media in their Grade 11 Milling Machine Techniques class at SMK Negeri 5 Padang. In order to improve student engagement and learning results, the study emphasizes how crucial it is to include technology into the teaching and learning process. This implies that the research findings offer valuable contributions to the development of more effective learning strategies by incorporating video media technology in vocational schools.